The Concept of Ulū al-Albāb in the Qur’an for Ethical Foundation in Artificial Intelligence Development - Mujib Abdurrahman; Asif Trisnani; Rezki Kaulan Maisurah; Hilma Radhia Mahmudah (Studia Quranika, 2026)
Artificial Intelligence (AI) has transformed human decision-making through automated systems, but its rapid development has also generated ethical challenges, including algorithmic bias, limited transparency, weakened accountability, and the erosion of moral agency. Contemporary AI ethics is predominantly grounded in secular–humanistic frameworks, which often lack a comprehensive spiritual and metaphysical foundation. This study aims to examine the Qur’anic concept of Ulū al-Albāb as a normative ethical framework that can enrich contemporary AI ethics. Employing qualitative library research with a thematic approach, the study analyzes Qur’anic verses concerning Ulū al-Albāb through the exegetical perspectives of Ibn Kathīr, al-Marāghī, Ibn ‘Āshūr, Fakhr al-Dīn al-Rāzī, and M. Quraish Shihab. The findings identify five interrelated ethical values embodied by Ulū al-Albāb: intellectual purity (lubb), reflective thinking, ethical discernment (ḥikmah), spiritual consciousness (taqwā), and commitment to the essence of truth. These values provide a normative ethical framework that reinforces human moral responsibility rather than functioning as technical algorithms in AI systems. The study concludes that Ulū al-Albāb offers a meaningful ethical bridge between Islamic intellectual tradition and technological innovation. It is recommended that future AI governance and ethical policy frameworks incorporate spiritually grounded ethical values alongside technical and regulatory approaches to promote more responsible and human-centered AI development.